ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN TERMOKIMIA DENGAN MENGGUNAKAN METODE PRAKTIKUM - Ayu Lestari; Yuni Fatisa (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research aimed at analyzing student critical thinking skill using practical work method on Thermochemistry lesson. It was conducted at the first semester of the eleventh grade of Islamic Senior High School of Diniyah Puteri Pekanbaru in the Academic Year of 2018/2019. It was using descriptive method and it was pre-experiment with one shot case study design directing to get the information about critical thinking skill appeared, to see student critical thinking skill that could be developed through practical work method on Thermochemistry lesson. The subjects of this research were the eleventh-grade students at the first semester in the Academic Year of 2018/2019. Purposive sampling technique was used in this research, and it was obtained a class comprising 20 students, and they were divided into 4 groups. Observation, interview, and documentation were the techniques of collecting the data. Final data analysis of observation sheet showed student critical thinking skill that the total percentage was 77.09% and it was on good category.